The Role of the Class Teacher on the Development of Social Interaction in Distance Learning - Pratiwi, Dian; Busyairi, A. (Elementary School Teacher, 2021)
This study aims to find out the role of teachers in the development of social interaction of students during distance learningin grade V students of SD Islam Imama Mijen Semarang City. This study uses a qualitative approach of descriptive type.Research subjects include principals, grade V teachers, and grade V students. Data collection using observation methods,interviews, and documentation. Data validity testing uses source triangulation and engineering triangulation, and timetriangulation. The results showed that the role of teachers including teachers as mentors, teachers as mediators andfacilitators, teachers as demonstrators, and teachers as evaluators influenced the development of social interactions duringdistance learning. The conclusion of this study was that the role of teachers influences the development of socialinteraction in distance learning of grade V students of SD Islam Imama Mijen Semarang. Teachers understand well andcorrectly about their role so as to develop student social interactions that include aspects of cooperation, communicative,and solidarity.Keywords: Role of teacher, Social interaction, Distance learning